Education for Adults. Landscape of the online IT Master’s Programs in Russia - D. I. Grits; A. M. Brudkova (Высшее образование в России)
The number of online master’s programs in Russia is growing by the year with IT programs leading the way. The online master’s programs engage working adults whose goal is to obtain a new profession or master the skills required for their professional development. In terms of governmental regulation in Russia, almost no distinction is drawn between on-campus and online master’s programs. The surge in the number of the latter is attributed to university digitalization which merely transfers traditional content and structure to a digital form. The authors being actively engaged in educational practice challenge this point of view as it becomes apparent that online master’s programs constitute a stand-alone phenomenon worth thorough investigation. The article in question scrutinizes the core features of 48 Russian online master’s programs in IT; an explanatory analysis of the phenomenon is conducted through the open and distance education theories and the concept of professional master’s program. It is concluded that online master’s programs in IT in Russia bear signs of open and distance education models. However, it is premature to claim it a new type of education.